PENGARUH OLAHRAGA BOLA BASKET TERHADAP DISIPLIN PADA ANAK - Arfandi, Muhammad; Pranoto , Nuridin Widya; Mukhtarsyaf, Fahd; Selviani, Iit (Jurnal IKEOR, 2026)
This research is motivated by the importance of developing disciplined character in children. This study aims to determine the effect of basketball on children’s discipline. Basketball, as a team sport, is believed to play a significant role in shaping children’s character, including aspects of discipline, teamwork, and aggressiveness control. This study employed an ex post facto design with a quantitative approach to analyze causal relationships based on events that have occurred without any direct treatment of the research subjects. The sample size for this study was 20 respondents, namely children who had participated in basketball activities for at least six months. The sampling technique used a total sampling method, so that the entire population that met the criteria were included as research respondents. The study collected data using self-administered questionnaires parents based on observations of children’s behavior in the home environment after participating in basketball practice. The data obtained were then analyzed using statistical procedures to test the effect of participation in basketball on children’s discipline levels. Based on the analysis, a significant relationship was identified variables of basketball and discipline. The regression test produced a significance value of 0.000 (<0.05), indicating that involvement in basketball significantly contributes to improving children’s discipline. In addition, the coefficient of determination (R Square) of 0.933 shows that 93.3% of the variation in discipline levels can be explained by basketball variables, while the remaining 6.7% is influenced by other factors outside the scope of this study.